KETERAMPILAN BERBICARA DALAM BAHASA LISAN BAGI MAHASISWA - Gusnayetti Gusnayetti (Ensiklopedia of Journal, 2021)
Students who have good speaking skills, the conversation will be easier to understand by listeners. Speaking supports reading and writing skills. Writing and speaking have in common, namely as language production activities and convey information. The ability of students to speak will also be useful in listening and understanding reading activities. The conclusion that can be drawn is that Talking is a system of audible and visible signs that utilize a number of muscles of the human body for the purpose and purpose of combined ideas or ideas. Speaking is a form of human behavior that utilizes physical, psychological, neurological, semantic, and linguistic factors. Suggestion: with the importance of the speaking aspect of teaching Indonesian especially for elementary school students, educators must be able to provide motivation to develop speaking skills in students.